Case report: Complex arterial findings in vascular ehlers-danlos syndrome with a novel COL3A1 variant and death at young age - Taurino, Jacopo; Micaglio, Emanuele; Russo Raucci, Annalisa; Zanussi, Monica; Chessa, Massimo; Udugampolage, Nathasha Samali; Carrera, Paola; Pappone, Carlo; Pini, Alessandro (Frontiers in Cardiovascular Medicine, 2023)
Vascular Ehlers-Danlos syndrome (vEDS) is a genetic disease caused by a pathogenic mutation in the COL3A1 gene. Despite its severe course, the rarity and extreme clinical variability of the disease can pose significant obstacles to a timely diagnosis. Early and accurate diagnosis may lead to improved patient outcomes by providing access to targeted pharmacological treatments like celiprolol and enhancing the management of vEDS-related complications. Herein, we report a patient harboring a novel de novo COL3A1 missense variant, in which the diagnosis was only possible belatedly due to delayed referral for genetic evaluation. The patient developed pulmonary complications, aneurysms, and vascular malformations, and died at the age of 26 years due to massive pulmonary bleeding.